Evaluating Formation and Bioactivity of New Sol-gel Bioactive Glass - Xuan Vuong, Bui (VNU Journal of Science: Natural Sciences and Technology, 2019)
This paper discusses the synthesis of three ceramic compositions: 50SiO 2 -50CaO (A), 45SiO 2 -45CaO-10P 2 O 5 (B) and 40SiO 2 -40CaO-20P 2 O 5 (C) (wt %) using the sol-gel technique. XRD analysis demonstrates that only sample C can form bioactive glass material. Treated temperatures and heated times were also evaluated. The analysis data show that bioglass 40SiO 2 -40CaO-20P 2 O 5 (wt %) can successfully elaborate when the ceramic powder is heated at 750 o C for 3 hours. ‘‘In vitro’’ experiment was effectuated to investigate the bioactivity of bioglass 40SiO2-40CaO-20P 2 O 5 by soaking powder samples in SBF solution. The obtained result confirms the formation of hydroxyapatite (HA) phase on glass surface after 15 days of immersion, in which HA formation orients following (211) and (222) miller planes in crystalline structure of HA phase. Keywords   Sol-gel, bioglass, hydroxyapatite, SBF, bioactivity. References [1] D.F. Williams, Definitions in Biomaterials, Consensus Conference for the European Society for Biomaterials, Chester, UK, 1986, Chapter 4. https://doi.org/10.1002/pol.1988.140260910 [2] L.L. Hench, Bioceramics: From Concept to Clinic, J. Am. Ceram. Soc. 74 (1991) 1487-1510. https://doi.org/10.1111/j.1151 2916.1991.tb07132.x [3] L.L. Hench, The story of Bioglass, J. Mater. Sci. Mater. Med. 17 (2006) 967-978. https://10.0.3.239/s10856-006-0432-z [4] X.V. Bui, H. Oudadesse, Y. Le Gal, A. Mostafa, P.Pellen and G. Cathelineau, Chemical Reactivity of Biocomposite Glass-Zoledronate, J. Aust. Ceram. Soc. 46 (2010) 24-28. https://www. austceram.com/volume-46-number-2-2010. [5] L.L. Hench, Genetic design of bioactive glass, J. Euro. Ceram. Soc. 29 (2009) 1257-1265. https://doi.org/10.1016/j.jeurceramsoc.2008.08.002 [6] S. Kumar, P. Vinatier, A. Levasseur, K.J. Rao, Investigations of structure and transport in lithium and silver borophosphate glasses, J. Sol. Stat. Chem. 177 (2004)1723-1737. https://doi.org/10.1016/j.jssc.2003.12.034 [7] Z. Hong, A. Liu, L. Chen, X. Chen, X. Jing, Preparation of bioactive glass ceramic nanoparticles by combination of sol–gel and coprecipitation method, J. Non-Crys. Sol. 355 (2009) 368-372. https://doi.org/10.1016/j.jnoncrysol.2008.12.003 [8] D.B. Joroch, D.C. Clupper, Modulation of zinc release from bioactive sol–gel derived SiO2‐CaO‐ZnO glasses and ceramics, J. Biomed. Mater. Res. Part A. 82A (2007) 575-588. https://doi.org/10.1002/jbm.a.31180 [9] J. Roman, S. Padilla, M. Vallet-Regi, Sol−Gel Glasses as Precursors of Bioactive Glass Ceramics, Chem. Mater. 15 (2003) 798-806. https:// 10.1021/cm021325c [10] J. Lao, J.M. Nedelec, Ph. Moretto, E. Jallot, Biological activity of a SiO2-CaO-P2O5 sol-gel glass highlighted by PIXE-RBS methods, Nuc. Ins. Meth. Phys. Res. Sec. B. 245 (2006) 488-493. https://doi.org/10.1016/j.nimb.2007.03.092 [11] M. Vallet-Regi, L. Ruiz-Gonzalez, I. Izquierdo, J.M. Gonzalez-Calbet, Revisiting silica based ordered mesoporous materials: medical applications, J. Mater. Chem. 16 (2006) 26-31. https:// 10.1039/B509744D [12] W. Xia, J. Chang, Preparation and characterization of nano-bioactive-glasses (NBG) by a quick alkali-mediated sol–gel method, Mater. Lett. 61 (2007) 3251-3253. https://doi.org/10.1016/j.matlet.2006.11.048 [13] R. Li, A.E. Clark, L.L. Hench, An investigation of Bioactive Glass Powders by Sol-Gel Processing, Trans. Ann. Meet. Soc. Biomater. 12 (1990) 231-239. https://doi.org/10.1002/jab.770020403 [14] J. Lao, J.M. Nedelec, P. Moretto, E. Jallot, Imaging physicochemical reactions occurring at the pore surface in binary bioactive glass foams by micro ion beam analysis, App. Mater. Inter. 6 (2010) 1737-1742. https://10.1021/am1002316 [15] A. Balamurugan, G. Balossier, S. Kannan, J. Michel, A.H.S. Rebelo, J.M.F. Ferreira, Development and in vitro characterization of sol–gel derived CaO–P2O5–SiO2–ZnO bioglass, Act. Biomater. 3 (2007) 255-262. https:// 10.1016/j.actbio.2006.09.005 [16] Z. Hong, A. Liu, L. Chen, X. Chen, X. Jing, Bioactive glass prepared by sol–gel emulsion, J. Non-Crys. Sol. 355 (2009) 119-123. https://doi.org/10.1016/j.jnoncrysol.2012.10.025 [17] O. Peital, E.D. Zanotto, L.L. Hench, Highly bioactive P2O5-Na2O-CaO-SiO2 glass-ceramics, J. Non-Crys. Sol. 292 (2001) 115-126. https://doi.org/10.1016/S0022-3093(01)00822-5 [18] J. Liu, X. Miao, Sol-gel derived bioglass as a coating material for porous alumina scaffolds, Ceram. Inter. 30 (2004) 1781-1785. https://doi.org/10.1016/j.ceramint.2003.12.120 [19] T. Kokubo, H. Takadama, How useful is SBF in predicting in vivo bone bioactivity, Biomater. 27 (2006) 2907-2915. https://10.1016/j.biomaterials.2006.01.017 [20] M. Dziadek, B. Zagrajczuk, P. Jelen, Z. Olejniczak, K.C. Kowalska, Structural variations of bioactive glasses obtained by different synthesis routes, Ceram. Inter. 42 (2016) 14700-14709. https://doi.org/10.1016/j.ceramint.2016.06.095 [21] R. Lakshmi, V. Velmurugan and S. Sasikumar, Preparation and Phase Evolution of Wollastonite by Sol-Gel Combustion Method Using Sucrose as the Fuel, Combust. Sci. Tech. 185 (2013) 1777-1785. https://doi.org/10.1155/2018/6213568 [22] G. Voicu, A. Bădănoiu, E. Andronescu1, C. M. Chifiruc, Synthesis, characterization and bioevaluation of partially stabilized cements for medical applications, Cen. Euro. J. Chem. 11 (2013) 1657-1667. https://10.2478/s11532-013-0297-1 [23] M.V. Regi, Ceramics for medical applications, J. Chem. Soc. Dal. Trans. 2 (2001) 97-108. https://10.1039/B007852M [24] G. Voicu, A.I. Bădănoiu, E. Andronescu, C.M. Chifiruc, Synthesis, characterization and bioevaluation of partially stabilized cements for medical applications, Cen. Euro. J. Chem. 11 (2013) 1657-1667. https://10.2478/s11532-013-0297-1 [25] M. Wu, T. Wang, Y. Wang, F. Li, M. Zhou, X. Wu, A novel and facile route for synthesis of fine tricalcium silicate powders, Mater. Lett. 227 (2018), 187-190. https://doi.org/10.1016/j.matlet.2018.05.029